Evaluating Reading Habit among Junior Secondary School Students in Ekiti State in Nigeria - Joseph, Babalola Olurotimi (Universitas Negeri Makassar, 2020)
Abstract The study evaluated reading habit among students in Ekiti State Secondary Schools. The study specifically examined the frequency and time of reading among Junior Secondary School students in Ekiti State, the extent students read, how teachers’ attitudes affect their students reading habits, and ways reading habit can be improved. The descriptive research design of the survey type was adopted in this study. The population for the study consisted all of the Junior Secondary School Students in public secondary schools in Ekiti senatorial district. The size of the sample was 200 students drawn from ten public secondary schools using multistage sampling technique. A self-structured questionnaire tagged Reading Habit Questionnaire (RHQ) was used to collect relevant data for the study. The responses obtained were collated and analyzed using descriptive statistics. The findings revealed that most of the students rarely read as majority of them spend less than 2 hours daily on reading. They settle down to read only when given assignments or when examination was near. Based on the findings, it is therefore recommended among others that parents should teach their children to start reading from an early age and should provide reading materials for them. Also, it was recommended that teachers should engage students in fervent reading and writing activities. Keywords: Reading, Habit, Library, Descriptive, Revealed Students Teachers